Sexual dimorphism of viscerocranium-A logistic model - Peixoto, Lucas del Vigna; Gomes, Stefany de Lima; Barbieri, Ana Amelia; Groppo, Francisco Carlos; Martins Schmidt, Cristhiane; Ulbricht, Viviane; Sassi, Carlos; Bedran de Castro, Joao Cesar; Tinoco, Rachel; Daruge Junior, Eduardo; Francesquini Junior, Luiz (Open Science Journal, 2021)
Introduction: Sex estimates are generally based on the evaluation of qualitative and quantitative aspects of anatomic structures, however, the latter has better reproducibility and reliability. Objective: Aiming to evaluate the viscerocranium as a tool for sexual prediction and verify the possibility of creation of a logistic regression model for sexual prediction. Materials and Methods: 167 craniums - 100 male and 67 female between 22 and 85 years old from a Brazilian university´s Biobank - were evaluated. Results: It was observed that of the measures carried out were presented as sexually dimorphic, except for the measures of the right frontozygomatic point – right zygion; left frontozygomatic point – left zygion. Besides, it was possible to create a logistic regression model Sex = [logits/Sex = -24.5 + (0.20 * Nasion - Naso spine) + (0.18 * Right zygion - Naso spine)]. Conclusion: It was concluded that the measures of the viscerocranium present themselves as a factor of sexual dimorphism and the quantitative method developed was 81.4% accurate.